Tourism Industry Attitudes towards National Parks and Wilderness: A Case Study from the Icelandic Central Highlands - Anna Dóra Sæþórsdóttir; Margrét Wendt; Rannveig Ólafsdóttir (Land, 2022)
National parks serve a dual purpose: they aim to protect pristine nature and they are intended to facilitate visitation and provide necessary services. However, as visitation increases, it becomes challenging to establish a balance between visitation and the preservation of nature. This paper aims to examine the attitudes of tourism service providers in Iceland towards a proposed national park in the Central Highlands of Iceland, where pristine nature and wilderness are the main attraction, as well as the grounds for conservation. A mixed methodological approach was applied with an online questionnaire survey among all day-tour operators and travel agencies in Iceland, along with 48 semi-structured interviews as follow-up for a deeper understanding. In total, 382 companies answered the online survey, representing a 40% response rate. The results demonstrate that there are mixed opinions on whether the establishment of a national park is the best way to maintain the qualities of the area, with various arguments for and against the national park. Nevertheless, most tourism service providers want to have a say in its governance. It is however important to remember that the tourism industry exploits nature as a market-driven commodity, as its voice must always be evaluated in light of this.